2009
DOI: 10.1039/b809150a
|View full text |Cite
|
Sign up to set email alerts
|

The Envirostat – a new bioreactor concept

Abstract: One major goal of biology is to provide a quantitative description of cellular physiology. This task is complicated by population effects, which perturb culture conditions and mask the behavior of the individual cell. To overcome these limitations, the construction and operation of a microfluidic bioreactor is presented. The new reactor concept guarantees constant environmental conditions and single cell resolution, thus it was named Envirostat (environment, constant). In the Envirostat, cells are contactless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 47 publications
1
67
0
Order By: Relevance
“…27 Kortmann et al used elaborate dielectrophoretic (DEP) trapping to determine growth rates of single yeast cells and bacteria cells. 21 Walden et al developed parallel trapping regions for bacteria cultivation of up to 300 cells in a monolayer. 28 The latter allows for population heterogeneity analysis of larger bacterial microcolonies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Kortmann et al used elaborate dielectrophoretic (DEP) trapping to determine growth rates of single yeast cells and bacteria cells. 21 Walden et al developed parallel trapping regions for bacteria cultivation of up to 300 cells in a monolayer. 28 The latter allows for population heterogeneity analysis of larger bacterial microcolonies.…”
Section: Introductionmentioning
confidence: 99%
“…19 Secondly, microfluidic devices for biotechnological single cell studies including, e.g., phenotypic population heterogeneity 20 and single cell growth. 20,21 Our intention is a combination of both approaches, to be specific, a microfluidic device allowing environmental reactor control at a defined culture volume and continuous single cell observation simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“… represents n-DEP response and the particle moves towards the part of the electric field with lower intensity [27].…”
Section: CMmentioning
confidence: 99%
“…The desired capabilities of single-cell arrays bear strong resemblance to random access memory (RAM) computer chips, including the ability to introduce and retrieve single cells from precise locations of the chip (writing data), and query the biological state of specified cells at future time points (reading data). Existing particle handling tools based on hydrodynamic 8-11 , optic 12-18 , electric [19][20][21][22] and magnetic [23][24][25][26][27][28][29][30][31][32][33][34][35][36] trapping forces can achieve parts of this desired functionality; however, no single technique to our knowledge encompasses the scalability, flexibility and automation that allows single-cell chips to perform with the level of integration of computer circuits.Our approach has significant similarities with magnetic bubble memory technology 37 , which was originally developed to store memory and implement logic through the precise manipulation of 'magnetization bubbles' in iron garnet films. Previous works demonstrated that magnetization bubbles could be moved along specific tracks and into desired storage locations by controlling the electrical and magnetic circuitry patterned on top of the garnet films.…”
mentioning
confidence: 99%
“…The desired capabilities of single-cell arrays bear strong resemblance to random access memory (RAM) computer chips, including the ability to introduce and retrieve single cells from precise locations of the chip (writing data), and query the biological state of specified cells at future time points (reading data). Existing particle handling tools based on hydrodynamic [8][9][10][11] , optic [12][13][14][15][16][17][18] , electric [19][20][21][22] and magnetic [23][24][25][26][27][28][29][30][31][32][33][34][35][36] trapping forces can achieve parts of this desired functionality; however, no single technique to our knowledge encompasses the scalability, flexibility and automation that allows single-cell chips to perform with the level of integration of computer circuits.…”
mentioning
confidence: 99%